PERSEPSI MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS UIN AR-RANIRY TENTANG PLAGIARISME TUGAS KULIAH - Syamsul Bahri; Ika Kana Trisnawati (Jurnal Ilmiah Didaktika, 2018)
This study aimed to investigate the student perceptions of plagiarism and the reasons that led to plagiarism in the students’ assignments. The population of the study included the students of English Education Department at UIN Ar-Raniry Banda Aceh, with 166 students randomly selected as the sample. Questionnaire was used as the instrument for collecting data. The data were then analyzed with the SPSS in order to obtain their descriptive statistics. The results of the study showed that there were various students’ perceptions about the notion of plagiarism and the underlying reasons for their plagiarism. It was generally understood that plagiarism wa the use of words/ideas of others recognized as one’s own. Further, the major causes of plagiarism in the assignments were due to lack of English language skills and lack of time management. In addition, the behaviors of lecturers and the university involvement in socializing the concept of plagiarism also became the causes for the higher proportion of academic dishonesty among the students. These findings are expected to be the input for the creation of campus policy so that academic integrity and better lecture system can be achieved in any university.